Update on Endovascular Therapy for Fibroids and Adenomyosis - Ozen, Merve; Patel, Ronak; Hoffman, Mark; Raissi, Driss (Seminars in Interventional Radiology, 2023)
Uterine fibroids and adenomyosis are prevalent benign neoplasms that can lead to serious deleterious health effects including life-threatening anemia, prolonged menses, and pelvic pain; however, up to 40% of women remain undiagnosed. Traditional treatment options such as myomectomy or hysterectomy can effectively manage symptoms but may entail longer hospital stays and hinder future fertility. Endovascular treatment, such as uterine artery embolization (UAE), is a minimally invasive procedure that has emerged as a well-validated alternative to surgical options while preserving the uterus and offering shorter hospital stays. Careful patient selection and appropriate techniques are crucial to achieving optimal outcomes. There have been advancements in recent times that encompass pre- and postprocedural care aimed at enhancing results and alleviating discomfort prior to, during, and after UAE. Furthermore, success and reintervention rates may also depend on the size and location of the fibroids. This article reviews the current state of endovascular treatments of uterine fibroids and adenomyosis.
Keywords: fibroid; adenomyosis; embolization; uterine artery embolization; interventional radiology